Are Consumers Really Willing to Pay More for a Favorable Country Image? A Study of Country-of-Origin Effects on Willingness to Pay - Koschate-Fischer, Nicole; Diamantopoulos, Adamantios; Oldenkotte, Katharina (Journal of International Marketing, 2012)
Price-related consequences of the country-of-origin COO) cue have received limited attention in extant literature. In this study, the authors draw from equity theory and cue utilization theory and investigate 1) whether a brand's COO affects a consumer's willingness to pay and 2) the extent to which the consumer's familiarity with the brand moderates this relationship. The results of three complementary experimental studies reveal that COO indeed has a positive impact on willingness to pay. Furthermore, the authors find a negative moderating influence of brand familiarity on the COO effect in a high-involvement setting but not in a low-involvement setting. The authors discuss the theoretical and managerial implications of the findings, and they identify directions for further research. ©2012. American Marketing Association.
WiSo-Import:2015-03-26:3220
Keywords: Brand familiarity; Country of origin; Experimental research; Willingness to pay